Effects of acute aerobic exercise on cytokines, klotho, irisin, and vascular endothelial growth factor responses in rheumatoid arthritis patients - Ercan, Zubeyde; Deniz, Gulnihal; Yentur, Songul Baglan; Arikan, Funda Bulut; Karatas, Ahmet; Alkan, Gokhan; Koca, Suleyman Serdar (Springer London Ltd, 2023)
Background Rheumatoid arthritis (RA) is a chronic inflammatory joint disease that causes cartilage and bone damage as well as disability. Aims The aim of this study was to examine the effects of acute aerobic exercise on cytokines such as serum interleukin-6 (IL-6), interleukin-1 beta (IL-1 beta), Tumor Necrosis Factor-alpha (TNF-alpha) and irisin, vascular endothelial growth factor(VEGF) and klotho in RA patients. Methods Forty RA patient and 40 healthy volunteers of the same age participated in this study. All participants walked on the treadmill for 30 minutes at 60-80% of maximal heart rate. Blood samples were taken before and immediately after the exercise. Serum levels of IL-6, IL1 beta, TNF-alpha and irisin, VEGF and klotho were measured by enzyme-linked immunosorbent analysis. Results Baseline levels of inflammatory cytokines, irisin, VEGF and klotho were found to be higher in RA patients compared to the control group. In both groups, there was an increase in serum klotho levels after exercise compared to baseline (p<0.05), while a decrease in IL1 beta, TNF-alpha levels were observed. While serum VEGF level decreased in RA group, it increased in the control group(p<0.05). Irisin levels decreased in both groups. IL-6 level did not change in the control group, while it increased in RA group. A single exercise session had an acute anti-inflammatory effect in RA patients. Conclusion It can be concluded that acute aerobic exercise can be beneficial for patients with RA through cytokine, irisin, klotho and VEGF levels, and also it can be safely implemented to the RA rehabilitation program for additional anti-inflammatory effects. Trial registration ClinicalTrials.gov: NCT04439682
Keywords: Acute aerobic exercise; Cytokine; Irisin; Klotho; Rheumatoid arthritis; VEGF